Cover Jurnal Fitopatologi Vol. 17 No. 5, September 2021 - Sri Hendrastuti Hidayat (Jurnal Fitopatologi Indonesia, 2021)
This editorial contains the front cover, editorial page, and back cover of the Indonesian Journal of Phytopathology, Vol. 17 No. 5, September 2021